Highly nitrogen doped carbon nanofibers with superior rate capability and cyclability for potassium ion batteries - Xu, Yang; Zhang, Chenglin; Zhou, Min; Fu, Qun; Zhao, Chengxi; Wu, Minghong; Lei, Yong (Nature communications, 2018)
Potassium-ion batteries are a promising alternative to lithium-ion batteries. However, it is challenging to achieve fast charging/discharging and long cycle life with the current electrode materials because of the sluggish potassiation kinetics. Here we report a soft carbon anode, namely highly nitrogen-doped carbon nanofibers, with superior rate capability and cyclability. The anode delivers reversible capacities of 248 mAh g –1 at 25 mA g –1 and 101 mAh g –1 at 20 A g –1 , and retains 146 mAh g –1 at 2 A g –1 after 4000 cycles. Surface-dominated K-storage is verified by quantitative kinetics analysis and theoretical investigation. A full cell coupling the anode and Prussian blue cathode delivers a reversible capacity of 195 mAh g –1 at 0.2 A g –1 . Considering the cost-effectiveness and material sustainability, our work may shed some light on searching for K-storage materials with high performance. The development of potassium ion batteries calls for cheap, sustainable, and high-performance electrode materials. Here, the authors report a highly nitrogen-doped soft carbon anode that exhibits superior rate capability and cyclability based on a surface dominated charge storage mechanism.